Desain Pengembangan Buku Ajar Sejarah Kebudayaan Islam Berbasis QR Code MA Mambaul Ulum Jombang - Aisa, Aufia; Latifah, Auliyatul; Rahmawati, Rina Dian (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
This research and development aims to (1) design and develop a more attractive QR Code-based Islamic Cultural History textbook with material that is easy to understand, equipped with pictures and videos that are appropriate to the material developed so as to encourage students to learn effectively. independently 2) determine the level of effectiveness of the QR Code-based Islamic Cultural History textbook. This research uses research and development methods. The samples tested were students from classes XI IPA and XI IPS. Data collection used validation questionnaires, response questionnaires, interviews, observations and documentation carried out at MA Mambaul Ulum Megaluh Jombang. The data analysis techniques used are qualitative and quantitative. Validation by media experts gave an assessment in the "very suitable" category, media experts and student results gave an assessment in the "suitable" category. So it can be concluded that the QR Code-based Islamic Cultural History textbook design is effective and suitable for use for teaching and learning activities for students.